Comparison of thermal and light performance in two typical Chinese solar greenhouses in Beijing - Xu, Fan; Shang, Chao; Li, Hongling; Xue, Xuzhang; Sun, Weituo; Chen, Hong; Li, Yinkun; Zhang, Zhenhe; Li, Xinxu; Guo, Wenzhong (International Journal of Agricultural and Biological Engineering, 2019)
Solar greenhouses have been used for producing vegetables in northern China during early spring, late autumn or over-winter. To improve the thermal performance of solar greenhouses, a traditional type and a retrofitted design were comparatively evaluated. In the retrofitted design, three adjustments were incorporated: the material and structure of the walls, south-facing roof angle, and structure of the north-facing back-roof. The results indicated that the thermal and light performance of the retrofitted greenhouse was much better than that of the traditional greenhouse. Specifically, the daily mean temperature, minimum air temperature, and soil temperature inside the greenhouses after retrofit ting were increased by 1.3, 2.4, and 1.9°C, respectively, meanwhile, the daily total solar radiation and PAR were increased by 28.2% and 9.2%, respectively. The wall temperature and its daily variation range were reduced with increasing depth and height. The characteristic analysis of heat storage and release indicated that higher locations have longer heat storage, and shorter heat release time in vertical direction, as well as a lower ratio of heat release to storage. In horizontal direction, the western wall has the shortest heat storage time but the highest heat release flux density. Altogether, the heat storage time of the wall is 1.5 h less than that of the soil. The heat storage flux density of the wall is 1.5 times of that of the soil, but the heat release flux is only 61% of the soil’s value. The total wall heat storage is half of that of the soil in the greenhouse; the total wall heat release amount is only a quarter of that of the soil. Therefore, the thermal environment of solar greenhouses can be further improved by improving the thermal insulation properties of the wall. Keywords: structural change, heat storage performance, heat flux, back wall, thermal environment DOI: 10.25165/j.ijabe.20191201.3829 Citation: Xu F, Shang C, Li H L, Xue X Z, Sun W T, Chen H, et al. Comparison of thermal and light performance in two typical Chinese solar greenhouse in Beijing. Int J Agric & Biol Eng, 2019; 12(1): 24–32.